Near-Fatal Asthma: Case Report in the Emergency Department of Hospital Santa Rosa: Asma casi fatal: Reporte de un caso en emergencia del Hospital Santa Rosa | 接近致命的哮喘：圣罗莎医院急诊科病例报告 - Rojas Pérez, William (2024)
Introduction: Asthma, classically, is defined as a chronic inflammatory disease of the airways; characterized by a history of respiratory symptoms, such as wheezing, shortness of breath, chest tightness, and cough, that vary over time and in intensity. Near-fatal asthma are situations in which asthma exacerbations can lead to cardiorespiratory arrest, orotracheal intubation and mechanical ventilation, admission to an intensive care unit (ICU); Knowing the characteristics and risk factors that predict this situation in a patient who arrives at the emergency room is very important for early action. Clinical case: We present a 23-year-old patient with a history of asthma since he was 5 years old and irregular treatment; with a stay in the ICU and on mechanical ventilation for almost fatal asthma 8 months before; the clinical signs and the arterial blood gas analysis predicted an almost fatal asthma condition, which is why it was decided to intubate and mechanically ventilate the patient, and then transfer to the ICU with a favorable evolution and discharge 9 days after admission. Conclusion: Patient who already had a previous admission for almost fatal asthma and admission to the ICU, persistence of desaturation in the face of rescue treatment for said pathology; determining factors for deciding rapid sequence orotracheal intubation and transfer to the intensive care unit; with remission of the admission clinical picture and prompt discharge of the patient.